Water basd Tourist Attractions at Parbaba White Sand Beach and Indah Situngkir Beach, Pangururan District, Samosir Regency, North Sumatra - Hasoloan Marpaung (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2021)
Water based tourism is one of the most interesting tours in Samosir Regency, especially since most of the administrative areas of ​​this regency are located on the lake island of Samosir Island, which is the fourth largest lake island in the world with an area of ​​63,000 hectares. On this island there are Parbaba White Sand Beach and Indah Situngkir Beach which facilitate tourists/visitors to enjoy and make the most of water based tourism activities by using a wide selection of water play equipments such as buoys to help swim, water bikes, canoes, banana and donut boats, speed boats and others. These two beaches are must-visit beaches for those who want to enjoy what to do in water based tourism. This study aims to find out how far the level of satisfaction of visitors/tourists with the services (intangible services) of water based tourism business personnels and secondly to find out the extent to which the level of satisfaction of visitors/tourists with water tourism facilities at Pasir Putih Parbaba and Pantai Indah Situngkir, Pangururan District, Samosir Regency, North Sumatra and other facilities. supporters. The research instrument which was designed in the form of a questionnaire consisted of 21 questions which was reduced to only 17 questions due to validity measure. The research instrument based on reliability test results 0.8346 which is greater than 0.70 (Cronbach's Alpha). A total of 100 respondents became the incidental sample in this study. It was found that the satisfaction level of tourists/visitors toward the whole products (both intangible and tangible products) which was (78.32) was in the category ‘good’. Separately, the satisfaction of tourists/visitors with intangible products (services) is: 77.91% while satisfaction of tourists/visitors with tangible products is 77.91 and both are in the category: good. Based on these two conclusions, suggestions are proposed that managers increase awareness of the importance of service quality (intangible products) at all levels starting from the leadership level (owner) to the lower levels such as parking attendant, restaurant waiter/res and others. In particular, parking attendants as employees with the lowest scores for service quality need to receive guidance and direction to increase tourist/visitor satisfaction scores. The second suggestion put forward is that efforts should be carried out in the form of community service jointly by all managers by moving all workers to clean the beach from various wastes including the amount of plastic type waste on the beach, especially in lake water that stretches 20 meters from the shore where the tourists/visitors enjoy water game activities (water based tourism).